Aboriginal Voices in Australian Literature (Journal of Teaching and Research in English Literature, 2020)
The paper “Aboriginal Voices in Australian Literature” provides a comprehensive overview of the rich cultural heritage and struggles of Aboriginal Australians, with a focus on their representation in literature, particularly through the works of Kim Scott. It delves into the historical context of colonization and its devastating impacts on Aboriginal communities, highlighting themes of cultural preservation, identity, and resistance. The paper examines the complexities of Aboriginal life before and after European contact, exploring issues such as forced assimilation, language loss, and the ongoing challenges faced by Indigenous peoples. Through an analysis of Scott's novels, including True Country, Benang, and That Deadman Dance, the paper elucidates the author's efforts to reclaim Aboriginal narratives and revitalize cultural traditions amidst the pervasive effects of colonialism. Additionally, the abstract touches upon the broader themes of postcolonialism, Indigenous rights, and the imperative of preserving Aboriginal languages and cultures for future generations.